Strategic Culture Cult of Defense: Dominant Culture in China's Salami Slicing Geopolitical Strategy - Paramesvari, Nyoman Sekar Ayu (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
China continues to try to establish norms in international dynamics, especially in Asia, with a